3D gradient echo snapshot CEST MRI with low power saturation for human studies at 3T. Issue 4 (15th November 2018) - Deshmane, Anagha; Zaiss, Moritz; Lindig, Tobias; Herz, Kai; Schuppert, Mark; Gandhi, Chirayu; Bender, Benjamin; Ernemann, Ulrike; Scheffler, Klaus
Abstract : Purpose: For clinical implementation, a chemical exchange saturation transfer (CEST) imaging sequence must be fast, with high signal‐to‐noise ratio (SNR), 3D coverage, and produce robust contrast. However, spectrally selective CEST contrast requires dense sampling of the Z‐spectrum, which increases scan duration. This article proposes a compromise: using a 3D snapshot gradient echo (GRE) readout with optimized CEST presaturation, sampling, and postprocessing, highly resolved Z‐spectroscopy at 3T is made possible with 3D coverage at almost no extra time cost. Methods: A 3D snapshot CEST sequence was optimized for low‐power CEST MRI at 3T. Pulsed saturation was optimized for saturation power and saturation duration. Spectral sampling and postprocessing (B0 correction, denoising) was optimized for spectrally selective Lorentzian CEST effect extraction. Reproducibility was demonstrated in 3 healthy volunteers and feasibility was shown in 1 tumor patient. Results: Low‐power saturation was achieved by a train of 80 pulses of duration tp = 20 ms (total saturation time tsat = 3.2 seconds at 50% duty cycle) with B1 = 0.6 μT at 54 irradiation frequency offsets. With the 3D snapshot CEST sequence, a 180 × 220 × 54 mm field of view was acquired in 7 seconds per offset. Spectrally selective CEST effects at +3.5 and –3.5 ppm were quantified using multi‐Lorentzian fitting. Reproducibility was high with an intersubject coefficient of variation below 10% in CEST contrasts. Amide and nuclear overhauser effect CEST effects showed similar correlations in tumor and necrosis as show in previous ultra‐high field work. Conclusion: A sophisticated CEST tool ready for clinical application was developed and tested for feasibility.